KCPR #45 [Interview with Roger Boyd, keyboardist of Head East] (1977)
Interview between the band Head East's keyboard player Roger Boyd and a KCPR DJ (Pete, or Frank Wilkinson?) [00:00:30] Introductions between Roger Boyd and interviewer [00:00:50] Recount of recently completed Head East tour [00:01:11] Cities of Head East's upcoming west coast tour [00:01:30] Q: Is Head East selling out their concerts? [00:02:09] Q: How did Head East get their name? [00:02:45] Q: What groups have influenced Head East's style? [00:03:08] Q: Have the members of the band been playing together for a long time? [00:03:47] Q: What does Head East consider to be their best song/album? [00:05:48] Q: Was 'Don't Let Me Sleep in the Morning' or other songs based on a personal experience? [00:06:36] Q: Do the band ever feel like they are running out of material? [00:06:58] Writing songs on the road [00:07:27] Q: How are Head East's albums selling? [00:08:14] Q: Did you have any formal keyboard training? [00:08:54] Q: Do you have a big collection of keyboards? [00:09:34] Gary Boyd station identification for KCPR [00:10:15] Thanks for the interview